Dampak Prediabetes Gestasional Dan Diabetes Gestasional Terhadap Perkembangan Otak Janin - Eke Nor Jannah; Yusri Dwi Lestari; Robiatul Munawaroh (Journal of Innovative and Creativity, 2025)
Gestational diabetes has emerged as a silent threat to fetal brain development. This study quantitatively analyzes the impact of gestational prediabetes and gestational diabetes mellitus (GDM) on fetal brain structure and neurocognitive outcomes through a Systematic Quantitative Literature Review of ten studies published between 2021 and 2025. The synthesis revealed significant morphometric alterations, including a reduction in corpus callosum thickness (−0.98 mm), cerebellar diameter (−9.5%), and enlargement of the cavum septum pellucidum (+0.7 mm) in fetuses exposed to GDM. Functionally, infants demonstrated lower cognitive and motor scores, with mean decreases of 8.7 and 6.2 points, respectively. The biological mechanisms involve oxidative stress, inflammation, fetal hypoxia, and decreased levels of Brain-Derived Neurotrophic Factor (BDNF), which collectively disrupt myelination and synaptogenesis. These findings underscore that maternal glycemic control during pregnancy functions not only as a metabolic safeguard but also as a critical neuroprotective intervention. This review highlights the urgency of implementing universal glucose screening, integrating fetal neurosonography in antenatal care, and developing maternal health policies focused on fetal brain protection as a foundation for healthier, cognitively resilient generations.